THE EFFECT OF HYDROCORTISONE ON OUTCOME AMONG PATIENTS WITH SEPTIC SHOCK IN INTENSIVE CARE UNIT WITH LARGE VOLUME THORACENTESIS - NAEEM, OM; ULLAH, A; BATOOL, S; SAGAR, RS; NAEEM, OA; ISLAM, HFU (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the effect of hydrocortisone on the outcome of patients with septic shock in the intensive care unit (ICU). A case-control study was conducted at the Pulmonology Department of Pak Red Crescent Medical College & Teaching Hospital, Lahore, from November 2022 to April 2023 on 200 patients presenting with septic shock to the ICU. The patients were divided into two groups: cases (who received hydrocortisone) and controls (who received standard septic shock therapy). Mortality, vasopressor-free days, and mean ICU stay were assessed between groups. The mean age of the patients in the study was 43.55±14.08 years. The mortality rate was significantly lower in the cases group compared to the control group. In the cases group, the mean ICU stay was 8.14±0.817 days, while in the control group, it was 8.97±0.77 days (P = 0.001). In the cases group, the patients had significantly longer vasopressor-free days (9.95±0.82 days); in the control group, it was 8.97±0.85 days (P = 0.0001). The use of hydrocortisone can significantly reduce the ICU stay as well as the need for vasopressors in septic shock patients. The study also found that it has a significant reduction in mortality.